Application of Micro-Nano Aeration and Automatic Feeding to Increase Growth and Feed Efficiency in Catfish (Clarias gariepinus) Cultivation - Nainggolan, Santi Rama (Cattleya Darmaya Fortuna, 2025)
The performance of intensive catfish farming is often limited by low dissolved oxygen (DO) levels and inaccurate feeding. This study evaluated the combination of micro-nano aeration (MNA) and time-based automatic feeding on the Specific Growth Rate (SGR), Feed Conversion Ratio (FCR), survival rate (SR), and feed cost per kg of biomass. A completely randomized design was used, with four treatments: K (conventional blower + manual feeding), A (MNA + manual feeding), P (conventional + auto-feeder), and AP (MNA + auto-feeder); each with three replications, for 8 weeks of maintenance. Water quality parameters (DO, temperature, pH, TAN) were monitored daily–weekly. Sample results showed that AP increased DO at 04.00 (4.2→6.8 mg/L), decreased FCR (1.60→1.25), increased SGR (2.6→3.1%/day), and SR (88→95%), and decreased feed cost/kg biomass (Rp24,000→Rp19,500). The combination of MNA and auto-feeder is recommended for intensive ponds with high stocking density.